A Development of Welding Tips for the Reflow Soldering Process Based on Multiphysics - Jatuporn Thongsri; Thodsaphon Jansaengsuk (My University, 2022)
A reflow soldering process (RSP) is generally implemented in advanced manufacturing factories for welding small electronic components together to create a product using heat generated at the welding tip (WT). Improper WT design and operating conditions may lead to defects in some products; therefore, optimizing both is immensely significant in developing the RSP. Accordingly, this article proposes a successful RSP development based on multiphysics in a hard disk drive factory consisting of transient thermal-electric and structural simulations. First, a new shape series WT was designed, and a conventional shape, parallel WT, was considered as a case study. Then, they were assembled and experimented with the RSP actual operating conditions to collect essential data. Next, the heat transfer was determined using a transient thermal-electric simulation (TES). The simulation results showed uneven WT temperatures depending on applied voltages, time, and shapes, which were consistent with the experimental results. The higher the applied voltage, the greater the temperature generated at the WT. Finally, after using TES results as loads, the structural simulation showed WT total deformations, which could be consistent with actually occurring defects. The findings from this research are a new design of series WT and proper multiphysics methodology for developing the RSP.
Keywords: Multiphysics; Transient (computer programming); Electronic Packaging and Soldering Technologies